Peran Pemuda Dalam Pengembangan Pariwisata Budaya Di Desa Wisata Pejeng Kangin, Kabupaten Gianyar - Dewi, Ketut Ayu Candra Mesiya; Sanjiwani, Putri Kusuma (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2024)
Youth has a role as well as a very strategic position in the progress of the nation and state in the future. Balinese youth have an important role in preserving Balinese traditional culture, especially in the participation of the younger generation in the development of Balinese cultural tourism. Youth is the main actor in maintaining and promoting the values of cultural tourism. Pejeng Kangin Tourism Village is one of the tourist destinations that develops cultural tourism. The Pejeng Kangin youth have great potential as creators of innovative ideas for the development and advancement of tourism. The aim of this research is to determine the existence of cultural tourism and the role of youth in the development of cultural tourism in the Pejeng Kangin Tourism Village. This research is a qualitative research with qualitative descriptive data analysis techniques. The data in this study were collected by observation, interview and documentation techniques. The informants of this study were 25 people who were youths from the Pejeng Kangin Youth Organization. The results of this study indicate that the role of youth can be seen in participation in implementation and implementation as well as participation in enjoying the results. The role of youth related to participation in making and making decisions as well as participation in evaluations is still lacking, so it needs to be optimized again for better social welfare and tourism development. Keywords: Role of Youth, Cultural Tourism, Pejeng Kangin Tourism Village